Efficacy and Tolerance of Intensity Modulated Radiation Therapy for Skull Base Meningioma - Brahimi, Youssef (Adv Radiat Oncol, 2019)
PURPOSE: The purpose of this study was to evaluate the efficacy and tolerance of normofractionated stereotactic radiation therapy (RT) and intensity modulated RT with helical tomotherapy for skull base meningioma. METHODS AND MATERIALS: Between January 2009 and 2014, 46 patients with skull base meningioma were treated with normofractionated intensity modulated RT in stereotactic conditions (50%) or with helical tomotherapy (50%). Most of the lesions were localized in the cavernous sinus (59%). The mean planning target volume was 47.2 mL (range, 1.1-223 mL). RESULTS: After treatment, 5 lesions exhibited a partial response radiologically and 39 lesions were stable. At the time of treatment, 35 patients were symptomatic with a mean of 2 symptoms per patient. The most frequent symptoms were visual impairment (41%), cranial nerve dysfunction (20%), and headache (16%). The median follow-up time was 42 months (range, 10-76 months). After RT, 71% of patients exhibited an improvement of at least 1 symptom with a median interval of 15.6 months (range, 5.3-30.5 months). The most frequent improved symptoms were cranial nerve deficits (47%), visual impairment (45%), and headache (42%).The clinical response was correlated with the clinical target volume (CTV) margin (P = .06), extended clinical follow-up time (P = .004), and larger planning target volume (P = .05) by univariate analysis. Taking in account correlation factors, in the multivariate analysis, only CTV was a favorable significant factor of clinical improvement (P = .049; hazard ratio: 5 95%; confidence interval, 1.1-28). We observed 3 cases of trigeminal nerve dysfunction at 4.2, 5.7, and 24.6 months; 2 cases of visual disturbance at 10.1 and 24 months; 2 cases of neurocognitive disorders at 12.9 and 35.2 months; and 1 case of stroke at 20.3 months. CONCLUSIONS: RT for skull base meningiomas is an effective and safe treatment, leading in most cases to clinical improvement. The addition of a CTV margin to meningioma volume improved the symptoms of patients.